Odpowiedź:
1. a) (1/9)*w
b) (e+e³)/2
c) (2/3)*n
2. a) -a+6b = -1*(-3)+6*2 = 3+12 = 15
b) 2y² -x(3y+7) = 2*4 -4(-6+7) = 8 -4*1 = 8-4 = 4
3. a) 5x+3-2x+7-4x-2 = -x+8
-x+8 = -1*(-2)+8 = 2+8 = 10
b) 2a+3b-4+3a-4b = 5a-b-4
5a-b-4 = 10 - (-0,1) - 4 = 10,1 - 4 = 6,1
4. 1-{1-[x-(x-1)-(1-x)+x]-(1-x)} = 1-{1-[x-x+1-1+x+x]-1+x} = 1-[1-2x-1+x] = 1-1+2x+1-x = x+1
5. a) 2a-5b+3
b) 5x-6y+9
c) 5x+2-7x+2 = -2x+4
6. a) (4a+3)(b+5) = 4ab + 20a + 3b + 15
b) (5a-b)(a-3) = 5a² - 15a - ab + 3b
c) (3x-y)(2x+y) = 6x²+3xy-2xy-y² = 6x² + xy - y²
d) (2xy+3x)(xy-2x) = 2x²y²-4x²y+3x²y-6x² = 2x²y² - x²y - 6x²